Evaluating the Propagation of Exceptions in the Service Oriented Architecture in .NET - Lima, José Alex Medeiros de; Sousa Neto, Eliezio Soares de; Lima, José Sueney de; Cacho, Nélio Alessandro Azevedo; Coelho, Roberta de Souza; Costa, Umberto Souza da (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2013: Anais do VII Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2013)
High dependability, availability and fault-toleranceare open problems in Service-Oriented Architecture (SOA). The possibility of generating software applications by integrating services from heterogeneous domains, in a seamless way, makes worthwhile to face the challenges inherent to this paradigm. In order to ensure quality in service compositions, some research efforts propose the adoption of verification techniques to identify and correct errors. In this context, exception handling is a powerful mechanism to increase SOA quality. Several research works are concerned with mechanisms for exception propagation on web services, implemented in many languages and frameworks. However, to the extent of our knowledge no work evaluates these mechanisms in SOA with regard to the .NET framework. The main contribution of this paper is the evaluation of exception propagation mechanisms in SOA applications developed within the .NET framework.